Mathematical language in the modeling learning process in the technologic course in fashion design: a case study at a private college in Recife-PE (Revista de Ensino em Artes, Moda e Design, 2020)
In Fashion Design, modeling requires professional knowledge of measurements, fabrics, sewing and sewing technologies, as well as knowing how to interpret basic mathematics data, shapes, trends and calculations. Therefore, mathematical concepts are relevant aspects in the processes of flat and three-dimensional modeling. This article aims to analyze, interdisciplinarily, from the student perspective, the relationship between knowledge of mathematics and modeling, in the teaching-learning process of a higher education course in Fashion Design Technology. To this end, a case study, exploratory-comparative, of a qualitative and quantitative nature was carried out in the Higher Technology Course in Fashion Design, at a private college in Recife-PE. It was found that students have a gap in relation to basic mathematical knowledge, recognize their difficulty and see interdisciplinarity as an alternative to solve this problem, because the low knowledge of Fashion Design students on mathematics interferes negatively in the adequate development of knowledge about modeling.